1997
DOI: 10.1007/pl00007561
|View full text |Cite
|
Sign up to set email alerts
|

Toxic oxidant species and their impact on the pulmonary surfactant system

Abstract: In this review the effects of oxidant inhalation on the pulmonary surfactant system of laboratory animals are discussed. Oxidant lung injury is a complex phenomenon with many aspects. Inhaled oxidants interact primarily with the epithelial lining fluid (ELF), a thin layer covering the epithelial cells of the lung which contains surfactant and antioxidants. In the upper airways this layer is thick and contains high levels of antioxidants. Therefore oxidant injury in this area is rare and is more common in the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
68
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(71 citation statements)
references
References 152 publications
1
68
1
Order By: Relevance
“…At present, the exact mechanisms by which surfactant alterations in I/R injury occur are not completely understood. It seems likely that toxic oxidant species like free radicals, which are known to be important mediators in I/R injury [4,33], interact with surfactant components, especially the surfactant apoproteins [34,35]. Plasma proteins entering the alveolar space during intraalveolar oedema formation are also known to inactivate endogenous [4,6] as well as exogenous surfactant [36], although the authors have recently shown that surfactant alterations also occur in lung regions free of oedema, indicating that these surfactant alterations are not merely a secondary consequence of intraalveolar oedema formation [16].…”
Section: Discussionmentioning
confidence: 99%
“…At present, the exact mechanisms by which surfactant alterations in I/R injury occur are not completely understood. It seems likely that toxic oxidant species like free radicals, which are known to be important mediators in I/R injury [4,33], interact with surfactant components, especially the surfactant apoproteins [34,35]. Plasma proteins entering the alveolar space during intraalveolar oedema formation are also known to inactivate endogenous [4,6] as well as exogenous surfactant [36], although the authors have recently shown that surfactant alterations also occur in lung regions free of oedema, indicating that these surfactant alterations are not merely a secondary consequence of intraalveolar oedema formation [16].…”
Section: Discussionmentioning
confidence: 99%
“…In ALI resulting from direct lung injury, alveolar epithelial cells are the first to be altered, while ALI resulting from indirect lung injury begins with alteration of capillary endothelial cells. Intra-alveolar oedema, together with other factors, such as reactive oxygen and nitrogen species and neutrophil elastase, leads to alterations in the pulmonary surfactant system, which, in turn, lead to the decreased compliance that can be observed in ALI patients [28][29][30][31][32][33][34]. Thus, the components of the blood-air barrier and the surfactant system are primary targets in ALI and are therefore the structures that should be addressed when assessing ALI using stereology.…”
Section: Histopathological Aspects Of Alimentioning
confidence: 99%
“…Thus, ozone toxicity is observed mostly in the lower airways. Ozone reacts with unsaturated C=C bonds, amino acids, and other chemical structures, and ozone exposure can lead to edema, inflammation, and epithelial cell damage, contributing to lung injury and pulmonary surfactant derangement (2). The components of pulmonary surfactant (a lipoprotein complex) essential for normal lung function are likely to be vulnerable to reaction with inhaled ozone.…”
mentioning
confidence: 99%